Towards sustainable national plant genetic resources programmes policy, planning and coordination issues: Proceedings of an international workshop, 10-18 May 2002, Zschortau, Germany - Engels, J.M.M.; Vodouhe, R.; Thompson, J.; Zannou, A.; Hehne, E.; Grum, M. (2000)
This workshop is designed for national PGR programme policy makers, planners and leaders, gene bank managers and other key stakeholders. It will raise awareness of issues that are vital components of the complex environment within which national PGR programmes must operate, and will explore options for national PGR programme planning and coordination. Networking at the sub-regional and regional level is facilitating collaborative efforts to conserve and to use plant genetic resources; and concerted efforts are being made to develop the protocols and agreements through which the critical issues of sovereignty and access to PGR can be managed. The workshop has the overall goal of promoting the development of effective plant genetic resources programmes in countries of Central and Western Africa, thereby advancing the implementation of the Global Plan of Action for the conservation and sustainable utilization of PGRFA, and contributing to the achievements of sustainable agricultural development, security and, thus, to economic development in your countries. West and Central Africa is a source of essential agricultural genetic diversity.